Hierarchical CuCo2S4 Nanoflake Arrays Grown on Carbon Cloth: A Remarkable Bifunctional Electrocatalyst for Overall Water Splitting. Issue 6 (17th March 2021) - Ren, Can; Chen, Yajie; Du, Lizhi; Wang, Qi; Li, Longge; Tian, Guohui
Abstract: Fabricating self‐supporting electrocatalysts with double functions for overall water splitting is a promising strategy for clean energy generation. Herein, spinel‐based CuCo2 S4 nanoflakes were grown vertically on carbon cloth (CC) substrate to obtain hierarchical self‐supporting CuCo2 S4 /CC electrocatalysts through a hydrothermal process. The influence of hydrothermal time on the surface morphology and electrocatalytic properties of the CuCo2 S4 /CC was investigated. The rational synthetic approach can significantly reduce the diffusion path and promote the transfer of charge. As a result, the optimized CuCo2 S4 /CC exhibits a significantly higher electrocatalytic activity than the control single metal sulfide catalysts (CoS1.097 /CC and CuS/CC) in 1.0 M KOH solution, and relatively overpotentials of 204 and 280 mV are demanded to generate a current density of 10 mA cm −2 for hydrogen evolution reaction and oxygen evolution reaction, respectively. The significantly enhanced electrocatalytic activity benefits from the synergetic effect of the fast charge transport and abundant catalytic active sites. Moreover, in an overall water splitting system, a two‐electrode setup constructed using CuCo2 S4 /CC as both cathode and anode shows a low voltage of 1.58 V at 10 mA cm −2 and high durability. This study provides a rational strategy for improving the overall water splitting performance by constructing self‐supporting spinel‐based catalysts. Abstract : Flying solo : Hierarchical CuCo2 S4 nanoflakes were grown on the carbon cloth (CC) to fabricate high‐efficiency CuCo2 S4 ‐based self‐supporting catalysts through a hydrothermal process. When CuCo2 S4 /CC was used to assemble a two‐electrode setup as both the cathode, a significantly higher overall water splitting performance and stability under alkaline condition is observed due to the synergetic effect of the easy charge transport and abundant catalytic active sites.